2017
DOI: 10.1158/1078-0432.ccr-16-0870
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived CCL2 Mediates Resistance to Radiotherapy in Pancreatic Ductal Adenocarcinoma

Abstract: Purpose Local tumor growth is a major cause of morbidity and mortality in nearly 30% of patients with pancreatic ductal adenocarcinoma (PDAC). Radiotherapy (RT) is commonly used for local disease control in PDAC, but efficacy is limited. We studied the impact of selectively intervening on RT-induced inflammation as an approach to overcome resistance to RT in PDAC. Experimental Design PDAC cell lines derived from primary pancreatic tumors arising spontaneously in KrasLSL-G12D/+;Trp53LSL-R172H/+;Pdx-1 Cre (KPC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(226 citation statements)
references
References 43 publications
5
221
0
Order By: Relevance
“…Notably, in vivo studies of human tumors have demonstrated that cancer cells can also release CCL2 (4, 13). The stimuli that trigger cancer CCL2 secretion are not fully understood, although in pancreatic cancer this may occur in response to treatment (45). While our data support other evidence from nerve repair studies showing that Schwann cells are an important source of CCL2, nerve invasion develops within the context of a complex tumor microenvironment in which there may be additional cellular sources of CCL2 that vary as a function of disease progression and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in vivo studies of human tumors have demonstrated that cancer cells can also release CCL2 (4, 13). The stimuli that trigger cancer CCL2 secretion are not fully understood, although in pancreatic cancer this may occur in response to treatment (45). While our data support other evidence from nerve repair studies showing that Schwann cells are an important source of CCL2, nerve invasion develops within the context of a complex tumor microenvironment in which there may be additional cellular sources of CCL2 that vary as a function of disease progression and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described murine PDAC cell lines derived from KPC mice backcrossed onto the B6 background were used including 152.PDA (derived August 2012) (10), 7940B.PDA (derived June 2013) (12), and 69.PDA (derived August 2012) (24). Cell lines were authenticated based on histologic analysis of the implanted cell line with comparison to the primary tumor from which the cell line was derived.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibiting the recruitment of myeloid cells to tumors using inhibitors of chemokine receptor signaling pathways (e.g. CCL2/CCR2) can enhance the efficacy of chemotherapy and radiotherapy (810). Myeloid cell depletion using a colony stimulating factor 1 receptor (CSF1R) inhibitor has also been shown to enhance the efficacy of chemotherapy in PDAC mouse models (11).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, macrophages are the most abundant infiltrating cell in the tumor stroma after tumor irradiation and exhibit M2 properties that suppress subsequent immune responses 53, 61, 62. Depleting macrophages with anti–colony stimulating factor 1 antibodies or chemokine ligand 2 blockade slowed growth and improved responses to immune therapy and ionizing radiation in a number of tumor models 63, 64. Apart from depletion, several strategies have been demonstrated to repolarize macrophages to an M1 phenotype, which restores adaptive immune control of tumors 65 .…”
Section: Immune System and Cancermentioning
confidence: 99%